2011
DOI: 10.1089/lap.2011.0211
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Retrocaval Ureter by Retroperitoneal Laparoscopic Ureteroureterostomy: Experience on 12 Patients

Abstract: Our results have demonstrated that retroperitoneal LUUS was a safe and effective procedure, and an excellent minimally invasive treatment option for RCU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
1
13
0
5
Order By: Relevance
“…The mean operative time was 82 minutes and the blood loss was minimal. Chen et al [23] reported the largest series of retroperitoneal laparoscopic ureteroureterostomy for RCU with 12 patients. No open surgery conversion was needed.…”
Section: Discussionmentioning
confidence: 99%
“…The mean operative time was 82 minutes and the blood loss was minimal. Chen et al [23] reported the largest series of retroperitoneal laparoscopic ureteroureterostomy for RCU with 12 patients. No open surgery conversion was needed.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [ 15 ] reported the largest series of retroperitoneal laparoscopic ureteroureterostomy for retrocaval ureter with 12 patients operated on. No open conversion was needed.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic UU has been reported for the treatment of benign ureteral strictures, iatrogenic injury during gynecological surgery, and retrocaval ureter [1] , [4] . UU is traditionally performed through open surgery, but it has recently been increasingly performed through several minimally invasive techniques, including laparoscopic, robot-assisted, and LESS UU [1] , [2] , [3] .…”
Section: Discussionmentioning
confidence: 99%